Harmonisasi Masyarakat dalam Tradisi Perayaan Idul Adha di Kampung Lilinta Kabupaten Raja Ampat - Ahmad Havid Jakiyudin; Muhamad Yusuf; Rachmad Surya Muhandy; Natasya Aulia Husain; Yotan Manga’pan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The aim of this study was to determine the implementation and the symbolic meaning of the Ari Kaut tradition at the Eid al-Adha celebration and also to understand the reason why the Ari Kaut tradition could strengthen the community harmonization in Lilinta Village. This research is qualitative with using social phenomenology paradigm. The procession was started with Takbir and taking the alms from the congregation which has become a common habit. The acts of Syar’a judge in managing the celebration of Ari Kaut tradition was his responsibility as a religious figure so the norm and religious value on the tradition which carried out are still maintained. Cultural preservation on the Ari Kaut tradition was shown by the acts of the community according to their expertise such as making meat Qurban together to be served which is a habit that existed for a long time. Panpon as a religious symbol has a meaning to increase togetherness among the community. Eid al-Adha celebration was accompanied by traditional dances which are effective to be used to preserving culture.